(untitled) (Research, Society and Development, 2022)
Objective: to describe the construction of a bundle for the prevention of Post-Intensive Care Syndrome in patients who survived hospitalization in the Intensive Care Unit. Methodology: This is a methodological, descriptive research with a quantitative approach. For the first moment, data collection (field research) was carried out through the analysis of medical records of patients admitted to the Intensive Care Center. The second moment was an integrative literature review in PubMed, LILACS and SciELO databases, which evaluated 7 studies that talk about the theme. Results: In total, 21 medical records of patients likely to have Post Intensive Care Syndrome were analyzed. The following results were obtained that promote the syndrome: preventive care of respiratory physiotherapy, pause in sedation and assessment of the possibility of extubation; short-term signs and symptoms; in the physical sphere, the most observed alteration was paresis; in the cognitive sphere, it was changes in sleep and wakefulness and, in the psychological sphere, it was anxiety. In view of the epidemiological analysis of the patients involved, the female sex was the most prevalent; the age group corresponded to 50-59 years; the most prevalent class of diagnoses, as a reason for hospitalization, was the postoperative period of general surgery and the length of stay in days that was equal to 11-15 days. All described, as steps of the prevention bundle, the “ABCDE” package. Conclusion: Finally, the bundle was designed to be applied in practice. This consists of the three spheres already mentioned and with care such as: bed exercises, sedation adjustment and pain assessment.